New electroanalytical method for the determination of trans-anethole in spices and sweets. (15th May 2023) - Jashari, Granit; Frühbauerová, Michaela; Mikysek, Tomáš; Švancara, Ivan; Metelka, Radovan; Sýs, Milan
Graphical abstract: Highlights: Significant improvement in voltammetric determination of trans–anethole in foodstuffs. Rapid, simple, and undemanding electroanalytical procedure. One–step sample preparation due to utilization of nonaqueous carbon paste electrode. Comparable results with reversed–phase high–performance liquid chromatography. Detailed description of trans–anethole electrochemical reaction mechanism. Abstract: A completely new method for the determination of trans –anethole (TAN) based on the anodic oxidation of this flavouring substance in pure acetonitrile using differential–pulse voltammetry has been developed. A nonaqueous carbon paste electrode bulk-modified with solid sodium dodecyl sulphate of 40 % ( w/w ) content was chosen as optimum. To propose TAN electrode reaction mechanism, its electrochemical behaviour was investigated at glassy carbon electrode in nonaqueous media. At optimum working conditions, the current response could be calibrated within a linear range 2–200 µmol L −1 TAN, a coefficient of determination of 0.9971, a sensitivity of 0.1122 µA L µmol −1, and a detection limit of 0.7 µmol L −1 . A satisfactory precision (relative standard deviation of 4 %) has been achieved. The validation performed by analysis of spices and sweets provided comparable results with reference reverse–phase HPLC with spectrophotometric detection, thus confirming the practical use of the developed voltammetric method in food analysis.